Concordance in Business Cycles - McDermott, C.; Scott, Alasdair (Washington, D.C. : International Monetary Fund, 2000)
We study the properties of a test that determines whether two time series comove. The test computes a simple nonparametric statistic for 'concordance,' which describes the proportion of time that the cycles of two series spend in the same phase. We establish the size and power properties of this test. As an illustration, the procedures are applied to output series from selected major industrial countries. We find limited evidence of widespread concordance for these countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Bar Code; Concordance Statistic; Random Walk; Standard Error; WP; United States